Regular meals - Mumbai Archive Project Team (Jio Institute, 2024)
During meals, Rakesh Bhalia engages and plays with his grandson. Their daily food typically includes rice, curry, and fish. However, they refrain from consuming fish or any other type of meat on Tuesdays.